Móldelos sistémicos de validación formal y ergonómica en los mangos de los cuchillos utilizados en el porcionado de cárnicos (2022)
This degree project is carried out with the purpose of validating the shape of the handle of the knife based on data and studies on users suffering from diseases musculoskeletal injuries caused by repetitive movements in the hand and doll in the meat portioning activity.